2018
DOI: 10.3389/fncel.2018.00119
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrative Mechanism in Anxiolytic Behavior Induced by Galanin 2/Neuropeptide Y Y1 Receptor Interactions on Medial Paracapsular Intercalated Amygdala in Rats

Abstract: Anxiety is evoked by a threatening situation and display adaptive or defensive behaviors, found similarly in animals and humans. Neuropeptide Y (NPY) Y1 receptor (NPYY1R) and Galanin (GAL) receptor 2 (GALR2) interact in several regions of the limbic system, including the amygdala. In a previous study, GALR2 enhanced NPYY1R mediated anxiolytic actions on spatiotemporal parameters in the open field and elevated plus maze, involving the formation of GALR2/NPYY1R heteroreceptor complexes in the amygdala. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 79 publications
3
40
0
Order By: Relevance
“…Furthermore, the effects achieved after the administration of GAL or NPYY1 agonist alone agree with the previous studies and support the prodepressant‐like role of GAL and the antidepressant‐like actions of the NPYY1 agonist in the FST (Kotagale et al, 2013; Kuteeva et al, 2008; Redrobe et al, 2002). These behavioral effects observed in the FST were independent of the motor activity since neither GAL, and NPYY1 agonist nor their coadministration has shown locomotor modifications (Narvaez et al, 2016, 2018, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, the effects achieved after the administration of GAL or NPYY1 agonist alone agree with the previous studies and support the prodepressant‐like role of GAL and the antidepressant‐like actions of the NPYY1 agonist in the FST (Kotagale et al, 2013; Kuteeva et al, 2008; Redrobe et al, 2002). These behavioral effects observed in the FST were independent of the motor activity since neither GAL, and NPYY1 agonist nor their coadministration has shown locomotor modifications (Narvaez et al, 2016, 2018, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…GALR2/NPYY1R heteroreceptor complexes significantly increase in density, as shown with PLA upon combined treatment with GAL and the NPYY1R agonist in the subgranular zone in the ventral hippocampus. The existence of GALR2/NPYY1R heteroreceptor complexes was described in several regions, including the amygdala and the dorsal hippocampus (Narvaez et al, 2016, 2018, 2015). Additionally, we described how heteroreceptor complexes, such as 5HT1A‐FGFR1, promote significant hippocampal plasticity effects linked to hippocampal function changes, including antidepressant actions (Borroto‐Escuela et al, 2012; Narvaez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,[74][75][76] Narvaez et al confirmed the interaction between GalR2 and NPYY1R in the dentate gyrus (DG) with enhancement of the antidepressive-like behavior mediated by NPY Y1R 77 and anxiolytic behavior. 78 Moreover, GalR1-GalR2 heteromer interaction with Neuropeptide Y Y2 (NPYY2) may be a key molecular mechanism for GAL and its GAL1-15. 79 Furthermore, GAL1-15 fragments facilitate GalR1-5-HT1AR heteroreceptor complexes formation in the raphehippocampal 5-HT neurons and affects serotonin release; GAL1-15 induces stronger effects than GAL to cause depression.…”
Section: Galanin In Depressionmentioning
confidence: 99%